Disturbed sleep as risk factor for the subsequent onset of bipolar disorder – Data from a 10-year prospective-longitudinal study among adolescents and young adults. (September 2015) - Ritter, Philipp S.; Höfler, Michael; Wittchen, Hans-Ulrich; Lieb, Roselind; Bauer, Michael; Pfennig, Andrea; Beesdo-Baum, Katja
Abstract: There is ample data suggesting that individuals with bipolar disorder more frequently suffer from disturbed sleep even when euthymic. Since sleep is a process that is crucial for affective homeostasis, disturbed sleep in healthy individuals may be a risk factor for the subsequent onset of bipolar disorder. Utilizing data from a large cohort of adolescents and young adults, this study tests the hypothesis that disturbed sleep constitutes a risk factor for the later onset of bipolar disorder. A representative community sample of N = 3021 adolescents and young adults (baseline age 14–24) was assessed using the standardized Composite International Diagnostic Interview and followed-up prospectively up to 3 times over up to 10 years. Disturbed sleep at baseline was quantified utilizing the corresponding items from the self-report inventory SCL-90-R. The compound value (insomnia-score) as an ordinal parameter for the severity of sleep disturbances was used to assess associations with the incidence of bipolar disorder among participants free of major mental disorder at baseline (N = 1943) using odds ratios (OR) from logistic regressions. Analyses were adjusted for age, gender, parental mood disorder and lifetime alcohol or cannabis dependence. Poor sleep quality significantly increased the risk for the subsequent development of bipolar disorder (OR = 1.75; p = 0.001). Regarding individual sleep items, trouble falling asleep and early morning awakening were predictive for the subsequent onset of bipolar disorder. Disturbed sleep in persons otherwise free of major mental disorders appears to confer an increased risk for the subsequent onset of bipolar disorder. Highlights: We evaluated the question whether a poor quality of sleep in healthy individuals increased the risk of subsequent bipolar disorder. A representative sample of n = 1943 was followed up over up to ten years. Symptoms of insomnia at baseline significantly increased the risk for subsequent bipolar disorder (OR = 1.75).